Telaah Hukum Tata Usaha Negara Dalam Sengketa Administratif dan Keabsahan Ijazah - Fani, Khairul; Sultan, Benny (Jurnal Ilmiah Kutei, 2026)
The controversy regarding President Joko Widodo’s academic degree has become a widely discussed issue in society and is often viewed from political and public opinion perspectives. However, this debate also has an important legal dimension that needs to be examined from the perspective of administrative law. This study aims to evaluate the status of diplomas as products of state administration and assess their potential classification as State Administrative Decisions (Keputusan Tata Usaha Negara/KTUN), as well as their legal implications for dispute resolution processes within administrative courts. This research employs a normative legal research method using secondary data in the form of primary legal materials, namely legislation, and secondary legal materials. The approach used consists of a statutory approach and a conceptual approach, which are then analyzed descriptively through interpretation. The findings of this study indicate that, normatively, a diploma exhibits characteristics similar to those of KTUN elements, namely being in written form, issued by an institution or official exercising governmental functions, in accordance with legal regulations, and being concrete, individual, and final, as well as capable of producing legal consequences. However, the classification of a diploma as an object of administrative dispute is not absolute and highly depends on its context of use, the legal effects it generates, and the legal standing of the parties involved. This study concludes that the debate concerning President Joko Widodo’s diploma is more appropriately viewed as an issue within the conceptual domain of administrative law rather than as an administrative dispute that can be directly brought before the Administrative Court.